Determining why continuous cropping reduces the production of the morel Morchella sextelata - Wei-Ye, Liu; Hong-Bo, Guo; Ke-Xin, Bi; Alekseevna, Sibirina Lidiya; Xiao-Jian, Qi; Xiao-Dan, Yu (Frontiers in Microbiology, 2022)
Artificial cultivation of Morchella sextelata and other morels is expanding in China, but continuous cropping reduces Morchella for unknown reasons. Here, we investigated soil that had been used or not used for M. sextelata cultivation for 0, 1, and 2 years. We found that the continuous cropping of M. sextelata substantially reduced the pH and the nutrient content of the hyphosphere soil and increased sclerotia formation by M. sextelata. Changes in the structure of bacterial and fungal communities were associated with levels of available nitrogen (N) and phosphorus in the soil. With continuous cropping, the richness and diversity of fungal and bacterial communities increased, but the abundance of Bacillus and Lactobacillus decreased and the abundance of pathogenic fungi increased. FAPROTAX analysis indicated that N cycle functions were enriched more with than without continuous cultivation, and that enrichment of N cycle and sulfate respiration functions was higher in the second than in the first year of cultivation. FunGuild analysis indicated that the functions related to pathotrophs and wood saprotrophs were enriched by M. sextelata cultivation. Overall, the results suggest that continuous cropping may reduce M. sextelata production by acidifying the soil and increasing the abundance of pathogenic fungi. Additional research is needed to determine whether increases in the abundance of pathogenic fungi and changes in soil chemistry result in the declines in production that occur with continuous M. sextelata cultivation.